DETERMINAN PEMILIHAN AUDITOR EKSTERNAL BERKUALITAS - Adi Setiawan, 11.05.52.0145; Alfasadun, Alfasadun (Students Journal of Accounting and Banking, 2015)
This study aims to examine the effect of the companys growth, external financing needs, leverage and firm size on the selection of qualified external auditors. The data used is the company went public in the period 2011- 2013. The researcher used purposive sampling and obtained a sample of 201 research data. The research data were then tested by logistic regression using SPSS 16 applications to test the effect of the companys growth, external financing needs, leverage and firm size on the selection of qualified external auditors. The results of this study indicate that: sales growth did not affect the election of auditors. External funding requirements, leverage and firm size has positive influence on the selection of auditors.Keywords: Growth, External Financing Needs, Leverage, Firm Size and The Selection of Qualified External Auditors